The Effect of Capital Structure on the Financial Performance of Islamic Banks: Mediation of Liquidity Risk - Nuzula, Nur Meilinda; Afendi, Arif; Mardhiyaturrositaningsih, Mardhiyaturrositaningsih (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2026)
The study uses liquidity risk as a mediating variable to look at the relationship between Indonesian Islamic banks’ capital structure and financial performance. A quantitative methodology was applied using secondary panel data from 13 Islamic commercial banks for the years 2021-2024. Regression of panel data and the Sobel test in EViews 12 were used for the analysis. This study measures financial performance using variables related to liquidity risk and structural capital. The findings demonstrate that capital structure significantly and favorably affects liquidity risk as well as financial performance. Furthermore, financial performance is favorably and strongly impacted by liquidity risk. The Sobel test results demonstrate that liquidity risk serves as a mediating component in part. Regarding the relationship between financial performance and capital structure. These results demonstrate that strong management of liquidity and efficient debt management can boost Islamic banks' profitability.